E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI SEBAGAI FAKTOR PENDORONG PENGAMBILAN KEPUTUSAN MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA - Evita Tri Wahyuni; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this study to obtain empirical evidence about the influence of e-commerce on decision making for entrepreneurship, the influence of the use of accounting information systems on decision making for entrepreneurship. This research was conducted at State Universities and Private Universities in the city of Malang. Data collection methods used in this study were the distribution of questionnaires. The data used in this study is primary data obtained by distributing questionnaires directly and through the google form link to 88 respondents using convenience sampling techniques. Analysis of the data used were multiple linear regression analysis. The result of this study indicate show that e-commerce has a positive effect on decision making for entrepreneurship, the use of accounting information systems has a positive effect on decision making for entrepreneurship.Keywords : E-Commerce, Accounting Information Systems, entrepreneurship.